Special Educators' Working Conditions in Self-Contained Settings for Students With Emotional or Behavioral Disorders: A Descriptive Analysis. (October 2019) - O'Brien, Kristen Merrill; Brunsting, Nelson C.; Bettini, Elizabeth; Cumming, Michelle M.; Ragunathan, Maalavika; Sutton, Rachel
Special education teachers (SETs) who teach students with emotional or behavioral disorders (EBD) in self-contained settings are often less qualified, more stressed and burned out, and more likely to leave teaching than other SETs, resulting in a less effective workforce teaching students with significant behavioral and academic needs. Working conditions are a lever by which outcomes can be improved for SETs in these settings, yet the extant research on SETs' working conditions in self-contained settings is scarce; no researchers have comprehensively examined these SETs' working conditions using a national sample. To fill this crucial gap in the literature, we surveyed a national sample ( n = 171) of SETs serving students with EBD in self-contained classes. We describe findings in terms of the working conditions that SETs experienced—social (e.g., administrator support, paraprofessionals, professional development) and logistical (e.g., instructional grouping, instructional resources, planning time)—providing implications for research, policy, and practice.